Considerations on minimum friction velocity - Akylas, Evangelos; Tsakos, Y.; Tombrou, M.; Lalas, D. P. (My University, 2003)
The concept of the minimum friction velocity is studied using three different methods of scalar averaging for the calculation of the stresses. Particular emphasis is given to the extraction of the influence of a non-zero ambient wind shear observed in field measurements. Data from three different experimental sites in Athens with high roughness values are analysed in order to provide information concerning the dependence of the dimensionaless minimum friction velocity on the dimensionless roughness length. Data from the BOREX-95 experiment have also been re-analysed according to the methodologies presented in this study. The results are compared to the large-eddy simulations that are considered to be a reference study on shear-free convection.
Keywords: Ambient wind shear; Convection; Large-eddy simulations; Vector and scalar averaging